Timing and determinants of the introduction of complementary foods in Kuwait: Results of a prospective cohort study - Scott, J.; Dashti, M.; Al-Sughayer, M.; Edwards, Christine (SAGE Publications Inc., 2015)
© The Author(s) 2014. Background: The early introduction of complementary foods is common in Middle Eastern countries but little is known about the determinants of this practice in this region. Objectives: This prospective cohort study conducted from October 2007 to October 2008 investigated the determinants of the very early (before 17 weeks) introduction of complementary foods in Kuwait and compared rates of this practice against rates reported in the mid-1990s. Methods: A total of 373 women were recruited from maternity hospitals in Kuwait City and followed to 26 weeks postpartum. Data on complementary feeding practices were available from 303 women. Multivariate logistic regression was used to estimate the association of very early introduction of complementary foods with infant sex and maternal characteristics including age, years of education, employment intentions at 6 months postpartum, parity, prepregnancy body mass index, and prepregnancy smoking status. Results: All infants had received complementary foods by 26 weeks of age, with 30.4% receiving complementary foods before 17 weeks of age. Women born in other Arabic countries were less likely to introduce complementary foods before 17 weeks (adjusted odds ratio [adj OR] = 0.40; 95% confidence interval [CI], 0.22-0.73) than women born in Kuwait. Women who were exclusively formula feeding at 6 weeks postpartum were less likely to introduce complementary foods before 17 weeks (adj OR = 0.40; 95% CI, 0.23-0.71) than women who were still breastfeeding. Conclusion: Compared to the mid-1990s, fewer infants in Kuwait were receiving complementary foods before 17 weeks. Nevertheless, all infants had received complementary foods by 6 months of age.